Tratamiento de las emisiones gaseosas provenientes del proceso de refinación de oro y plata en la Empresa Minera Orenas S. A. - Peña Sisalima, Juliana R. (2013)
Gaseous emissions into the atmosphere emanating greatly contribute to environmental pollution, which comes from refining of gold and silver, with the products of the exothermic reaction between nitric acid, sulfuric acid, hydrochloric acid and the precipitate recovered from electrolysis cells (electrodeposition) obtained elution system Orenas S A Mining Company dedicated to the processing of gold ores in the canton Camilo Ponce Enriquez La Lopez in the province of Azuay.